Embryo recovery and pregnancy rates after the delay of ovulation and fixed time insemination in superstimulated beef cows - Gouveia Nogueira, Marcelo F. [UNESP]; Barros, Breno J.P. [UNESP]; Teixeira, Andrey B. [UNESP]; Trinca, Luzia A. [UNESP]; D'Occhio, Michael J.; Barros, Ciro Moraes [UNESP] (My University, 2002)
The aim of this study was to evaluate the effect of delaying ovulation subsequent to superstimulation of follicular growth in beef cows (Bos indicus) on embryo recovery rates and the capacity of embryos to establish pregnancies. Ovulation was delayed by three treatments using either progesterone (CIDR-B®) or a GnRH agonist (deslorelin). Multiparous Nelore cows (n = 24) received three of four superstimulation treatments in an incomplete block design (n = 18 per group). Cows in Groups CTRL, P48 and P60 were treated with a CIDR-B device plus estradiol benzoate (EB, 4 mg, i.m.) on Day-5, while cows in Group D60 were implanted with deslorelin on Day-7. Cows were superstimulated with FSH (Folltropin-V® 200 mg), from Day 0 to 3, using twice daily injections in decreasing amounts. All cows were treated with a luteolytic dose of prostaglandin on Day 2 (08:00 h). CIDR-B devices were removed as follows: Group CTRL, Day 2 (20:00 h); Group P48, Day 4 (08:00 h); Group P60, Day 4 (20:00 h). Cows in Group CTRL were inseminated at 10, 20 and 30 h after first detected estrus. Ovulation was induced for cows in Group P48 (Day 4, 08:00 h) and Groups P60 and D60 (Day 4, 20:00 h) by injection of LH (Lutropin®, 25 mg, i.m.), and these cows were inseminated 10 and 20 h after treatment with LH. Embryos were recovered on Days 11 or 12, graded and transferred to synchronized recipients. Pregnancies were determined by ultrasonography around Day 100. Data were analyzed by mixed procedure, Kruskal-Wallis and Chi-square tests. The number of ova/embryos, transferable embryos (mean ± S.E.M.) and pregnancy rates (%) were as follows, respectively: Group CTRL (10.8 ± 1.8, 6.1 ± 1.3, 51.5), P48 (12.6 ± 1.9, 7.1 ± 1.0, 52.3), P60 (10.5 ± 1.6, 5.7 ± 1.3, 40.0) and D60 (10.3 ± 1.7, 5.0 ± 1.2, 50.0). There were no significant differences among the groups (P > 0.05). It was concluded that fixed time AI in association with induced ovulation did not influence embryo recovery. Furthermore, pregnancy rates in embryos recovered from cows with delayed ovulation were similar to those in embryos obtained from cows treated with a conventional superstimulation protocol. © 2002 Elsevier B.V. All rights reserved.
Keywords: Delayed ovulation; Deslorelin; Embryo transfer; Progesterone; Superovulation; deslorelin; estradiol; estradiol benzoate; follitropin; gonadorelin; luteinizing hormone; progesterone; prostaglandin; drug derivative; triptorelin; animal; animal disease; animal experiment; artificial insemination; breeding success; cattle; controlled study; cow; drug effect; echography; embryo; embryo transfer; estrus; female; fertilization; luteolysis; nonhuman; ovary; ovary follicle; ovulation; ovulation induction; physiology; pregnancy; pregnancy rate; pregnancy test; superovulation; surgical technique; transplantation; Bos; Bos indicus; Animals; Cattle; Embryo; Embryo Transfer; Estradiol; Female; Follicle Stimulating Hormone; Gonadotropin-Releasing Hormone; Insemination, Artificial; Luteinizing Hormone; Ovarian Follicle; Ovary; Ovulation; Ovulation Induction; Pregnancy; Pregnancy Tests; Tissue and Organ Harvesting; Triptorelin